The Effect of Authority Delegation on Decision Making Effectiveness in DAL Group in North Khartoum, Sudan - Manal Hussain Mohammed Eltigani ,; Ashraf A. Ahmed Hassan,; Maruod E. Maruod, (IJRDO - Journal of Social Science and Humanities Research, 2020)
The current study was conducted in DAL group in Khartoun North in the period between 2015-2018. The objectives of the study were to reveal the role of authority delegation in enhancing the administration in making decisions. Reveal the need for authority delegation in business organization in quick decision taking. Primary data were collected via constructed questionnaire covering 105 DAL group directors and employees selected randomly. Descriptive statistics was used to analyze collected data. The results showed that, 71.4 % of respondents were agreed that there is effective authority delegation. 81.9 % of respondents were agreed that delegated persons had high efficiency. 58.1 % of respondents agreed that authority delegation make decision in the right time, 37.0 % of respondents agreed that the centralization of authority detain decision taking, and 42.0 % were disagreed. Study correlation results showed that, there was strong correlation between authority’s delegation and the effectiveness of decision making, second finding there was positive statistical indication between authority delegation and the quickness of taking decision. Study concluded that proved statistical indicator between authority delegation and the effectiveness of taking decision at proper time, results proved strong statistical correlation between authority delegation and the quickness of decision taking. Study recommended more authority delegation to assure employees contribution in decision making, and also to assure the continuation of activities even in the absence of senior chief officer.